Measuring оf regional democracy in new European democracy states (on example of Eastern Partnership countries) (Part II) - Panchenko, T. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The paper proposed an evaluation instrument for measuring of regional democracy in new democracies and it is tested on example of six countries of Eastern Partnership. Index of regional democracy consists of seven indicators, which measure different aspects of subnational processes with focuses on regional tier. This part is represented the four from seven indicators - fiscal autonomy, representation, national and international relations, participation.  Conclusions about the level of regional democracy in the countries are formulated on the base scoring of all indicators and using of corrective factors.